1990
DOI: 10.1007/bf00145788
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of hepatitis a in young adults in central Italy

Abstract: Between September, 1988 and January, 1989 a common source outbreak of 47 cases of serologically confirmed hepatitis A occurred in a town of central Italy. Thirty-eight cases were primary, three co-primary and six secondary. The highest age-specific attack rate was seen in subjects aged 15-24 years (120 per 100,000); the mean age of cases was 24.6 years and the median age was 22 years. A matched triplet case-control study showed significant association between the disease and consumption of either raw mussels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…In fact, this is the largest virusassociated outbreak of food poisoning ever reported. Smaller outbreaks have been reported from the United States, Italy, and Australia [8,[9][10][11][12][13]. The fairly protracted incubation period (mean duration, 4 weeks) of HAV infection makes it very difficult to determine the association with a particular food vehicle in sporadic cases.…”
Section: Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this is the largest virusassociated outbreak of food poisoning ever reported. Smaller outbreaks have been reported from the United States, Italy, and Australia [8,[9][10][11][12][13]. The fairly protracted incubation period (mean duration, 4 weeks) of HAV infection makes it very difficult to determine the association with a particular food vehicle in sporadic cases.…”
Section: Virusesmentioning
confidence: 99%
“…One of the first recognized outbreaks associated with the consumption of raw oysters was described in 1816 by the French physician J. P. A. Pasquier [2]. He described Clams, oysters, mussels [8][9][10][11][12][13] Vibrio parahaemolyticus 5 669 USA, Canada Oysters, clams [14] Vibrio cholera 4 120 Malaysia, Italy, USA "Shellfish," "bivalves," oysters [15,16] Vibrio vulnificus 1 72 USA Oysters [17] Vibrio mimicus 1 17 USA Oysters [18] Vibrio hollisae 1 2 USA Oysters [19] Salmonella species 3 98 Singapore, UK, Japan Oysters, cockles [20] Shigella flexneri 1 40 France Shrimps, mussels - Physiology. Understanding the physiology of the bivalves helps clarify why people become infected after eating raw shellfish.…”
mentioning
confidence: 99%
“…In fact, this is so far the largest virus-associated outbreak of food poisoning ever reported. Smaller outbreaks have been reported worldwide (10,13,24,27,29,35,37). Several issues, such as the fact that fecal HAV excretion precedes the onset of symptoms, together with the difficulties in completely removing and/or inactivating viruses through sewage treatment (6,7), make hepatitis shellfish-borne outbreaks hard to prevent if the virus is circulating among the population.…”
mentioning
confidence: 99%
“…Several studies reported that the consumption of contaminated water and food are a probable source of Salmonellosis, Giardiasi, Hepatitis A and Criptosporidiosis outbreaks. (Mancini et al, 2010;Conio et al 2000;Ballone et al, 2001;Stroffolini et al 1990;Leoni et al 1998;Selvaggi et al 1996). Indicator organisms are commonly used to evaluate the microbiological quality of aquatic ecosystems (Berg 1978;Grabow 1996;EU 2006;Tyagi et al 2006).…”
Section: Microbiological Indicators and Sanitary Significance For Hummentioning
confidence: 99%